Relugolix Combination Therapy Reduced Uterine Fibroid-Associated Pain in Two Phase 3 LIBERTY Studies [32B]. (May 2020) - Stewart, Elizabeth A.; Lukes, Andrea S.; Venturella, Roberta; Li, Yulan; Hunsche, Elke; Al-Hendy, Ayman
Abstract : INTRODUCTION: Currently, pain (menstrual and non-menstrual), is poorly studied in women with uterine fibroids (UF). Relugolix combination therapy (Relugolix-CT; once-daily relugolix 40 mg, estradiol 1.0 mg, and norethindrone acetate 0.5 mg) significantly improved UF-associated heavy menstrual bleeding in the two LIBERTY randomized phase 3 trials. METHODS: In the LIBERTY 1 and 2 Institutional Review Board-approved studies, a key secondary endpoint was the proportion of women with no/minimal pain (maximal pain score ⩽1 on the 0–10 numerical rating scale [NRS] during the last 35 days of treatment) in the pain-evaluable population (women with maximum pain NRS ≥4 during the 35 days prior to randomization). Pain was also evaluated on menstrual bleeding and on non-menstrual days during the last 35 days of treatment. Treatment comparisons were performed in both studies and the pooled dataset using the Cochran–Mantel–Haenszel test stratified by baseline menstrual blood loss volume. RESULTS: After 24 weeks of treatment, a significantly greater proportion of pain-evaluable patients in the Relugolix-CT groups (43.1% and 47.1% in LIBERTY 1 and 2, respectively) had no/minimum UF-associated pain during the last 35 days of treatment compared with placebo (10.1% and 17.1%, respectively; P <.0001). The proportions of women with no/minimum dysmenorrhea and non-menstrual pain were significantly higher with Relugolix-CT (pooled data: 65.0% and 44.6%, respectively) vs placebo (19.3% and 21.6%, respectively). CONCLUSION: Over 24 weeks, once-daily Relugolix-CT reduced UF-associated pain, with a more pronounced effect on menstrual vs non-menstrual pain. Thus, Relugolix-CT improved two common symptoms (menstrual bleeding and pain) associated with UF.